NIAT WAKAF TUNAI ONLINE PADA MAHASISWA EKONOMI ISLAM - Hanna; Widiyanti, Dwi Retno (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
Indonesia with a majority Muslim community makes the potential for cash waqf very large. According to the National Committee for Islamic Economics and Finance (KNEKS), the potential for cash waqf could reach IDR 180 trillion, but the realization of waqf is still far below the existing potential. In general, the practice of waqf can help the socio-economic development of the Muslim community and distribute wealth among the community because waqf is intended to fund and maintain Islamic institutions such as madrasas, schools, universities and other public services. The research was conducted with the aim of knowing the effect of income, knowledge, trust, and convenience of students on students' intentions to do cash waqf at online waqf institutions. This study uses a descriptive quantitative approach with logistic regression analysis method. The sampling method used was Non-Probability sampling with Purposive Sampling Technique, and found 176 according to Isaac and Michael's formula from the total population of Islamic Economics Students from the batch of 2015 until 2021. From the R-Square test, it is known that the independent variables in the study can explain 64.2% of the related variables and the rest can be explained by variables outside of the study. In addition, the results of this study indicate that the convenience variable is significant to the students' intention to perform waqf through money. While the variables of income, knowledge, and trust have no significant effect on students' intentions in conducting cash waqf through online waqf institutions.